2003
DOI: 10.1002/j.2162-6057.2003.tb00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Need for Uniqueness, Need for Cognition, and Creativity

Abstract: This study examined two neglected dispositional contributions to creativity, namely needs for uniqueness and cognition. Multiple measures of creativity were used including an inventory of creative accomplishments, preference for complex visual figures (a measure similar to the Barron‐Welsh Art Scale), unconventional rather than popular word associations, and consensually‐assessed creative products. The latter included creative drawing, creative writing (a TAT story), richness of a photo essay about the self an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(156 citation statements)
references
References 59 publications
7
144
0
Order By: Relevance
“…The activities scale of the ICAA was constructed in the style of existing scales that measure everyday creativity such as the revised CBI (Dollinger, 2003;Hocevar, 1979) or the BICB (Batey, 2007). Participants report on a 5-point scale how often they carried out certain activities within the last 10 years (never, one to two times, three to five times, 5-10 times, and more than 10 times).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activities scale of the ICAA was constructed in the style of existing scales that measure everyday creativity such as the revised CBI (Dollinger, 2003;Hocevar, 1979) or the BICB (Batey, 2007). Participants report on a 5-point scale how often they carried out certain activities within the last 10 years (never, one to two times, three to five times, 5-10 times, and more than 10 times).…”
Section: Methodsmentioning
confidence: 99%
“…Everyday creativity is 'defined in terms of human originality at work and leisure across the diverse activities of everyday life' (Richards, 2010, p. 190). Popular measures of everyday creativity are the revised Creative Behavior Inventory (CBI; Dollinger, 2003; based on the original CBI by Hocevar, 1979) and the Biographical Inventory of Creative Behavior (BICB; Batey, 2007) (for a review, see Silvia et al, 2012). Both inventories contain lists of various creative activities (e.g.…”
Section: Everyday Creativitymentioning
confidence: 99%
“…Research has shown that creative performance in various domains is promoted by state intrinsic motivation (Amabile, 1996) although the effects of state extrinsic motivation are less well understood (Eisenberger & Shanock, 2003). Additionally, in several different domains creative behavior has been associated with stable individual differences in intrinsic and extrinsic motivational orientations in schoolwork and employment (Amabile, Hill, Hennessey, & Tighe, 1994;Kaufman, 2002) and with need for cognition, which Cacioppo and Petty (1982) define as trait intrinsic motivation to engage in effortful cognitive processing (Dollinger, 2003;Tierney, Farmer, & Graen, 1999). In the present study, we measured these types of trait motivational orientation.…”
Section: Volume 40 Number 3 Third Quarter 2006mentioning
confidence: 99%
“…Of the 105 studies that relied on judges, about 60% (n ¼ 64) clearly indicated the use of Consensual Assessment Technique (CAT; Amabile, 1982) and 40% (n ¼ 41) only mentioned the use of judges (e.g., Friedrich & Mumford, 2009;Palmiero, Cardi, & Belardinelli, 2011). CAT was also applied to score responses to divergent thinking tests in several studies (n ¼ 16, 8%; e.g., Dollinger, 2003;Friedman, 2009;Friedman, Forster, & Denzler, 2007;Kousoulas, 2010).…”
Section: Review Of Research Methodologies and Methodsmentioning
confidence: 99%